Eficacy of Water Clover Extract (Marsilea crenata) Against Blood Estrogen Progesteron Balance, Blood Calcium Levels and Impact on Dense of Bone Tissue of Rat (Rattus novergicus) - Pratiwi Trisunuwati (Research Journal of Life Science, 2017)
The potential of phytoestrogen for the stabilized of low condition blood estrogen hormone much more important to be sudy. So the aim of this reseach were to find an natural herbal active compounds Water Clover Extract (Marsilea crenata) which contain phytoestrogen isoflavones as an alternative invasive treatment against menopause women and subestrus in dam of livestock. The other advantage is that could be potential to develop as alternative compound against animal with low level of blood calcium that relevance on progesterone level, because there was some rising of exogen phytoestrogen. This research is true experimentally post test control design based on completely randomized design. The old females white rat (Rattus norvegicus), divided into 5 groups challenges with 2 ml each Marsilea crenata extract in different concentration such as 6.25%, 12.5%, 25%, 50% given by gastric sonde along 23 days, compare negative control group. Level of blood calcium using SSA showed increase in all the treatment (P<0,05)  started on 12,5%, lower the progesterone and raised estrogen hormone as natural balance. To find about effect of Calcium toward osteogenesis used to determine the description of histopathologis (HE) bone tissue that impact on bone density. Histology os humerus showed that have impact on dense of bone tissue. The conclusion of this research were Marsilea crenata juice plays a role in increasing toward blood calcium levels and surely increase bone density in animal laboratory (Rattus norvergicus), supporting by blood  estrogen progesterone  balance. The suggestion was Marsilea crenata extract could be potential as a substance to increase estrogenic progesterone balance and rise blood calcium both in human and animal.